Xen 63 versus Preserflo MicroShunt implant in patients with primary open-angle glaucoma - José María Martínez-de-la-Casa; Antonio Pascual-Santiago; Laura Morales-Fernandez; Federico Saez-Frances; Sofia Garcia-Saenz; Noemi Guemes-Villahoz; Ruben Sanchez-Jean; Carmen Mendez; Julian Garcia-Feijoo (Scientific Reports)
Abstract This study compared the efficacy safety profiles of the Xen 63 and Preserflo MicroShunt devices, both standalone, in patients with primary open-angle glaucoma (POAG). It is a retrospective and single-center study conducted on consecutive on patients with medically uncontrolled POAG who underwent either a standalone Xen 63 or a standalone Preserflo and had a 12-month follow-up visit. The primary outcome was the mean IOP at month-12. Sixty eyes were included, 30 eyes in each Xen 63 and Preserflo groups, respectively. Preoperative IOP was significantly lowered from 20.8 ± 3.6 mmHg and 19.1 ± 3.8 mmHg to 14.2 ± 4.5 mmHg and 12.8 ± 2.3 mmHg in the Xen 63 and Preserflo groups, respectively (p < 0.0001 each, respectively); without significant differences between groups (p = 0.1346). Preoperative number of ocular-hypotensive drugs was significantly reduced from 2.3 ± 0.6 to 0.2 ± 06 drugs and from 2.3 ± 0.7 to 0.3 ± 0.6 drugs, in the Xen 63 and Preserflo groups, respectively (p < 0.0001 each, respectively); without significant differences between groups (p = 0.5212). Regarding safety, one (3.3%) eye in the Preserflo group required a device removal due to maculopathy. Three (10.0%) eyes in the Xen 63 group underwent needling. In conclusion, both the Xen 63 and the Preserflo devices effectively and safely reduced IOP and the requirement for IOP-lowering medications, exhibiting comparable IOP levels after 12 months.